Binary encoded computer generated holograms for temporal phase shifting - Amphawan, Angela (2011)
The trend towards real-time optical applications predicates the need for real-time interferometry.For real-time interferometric applications, rapid processing of computer generated holograms is crucial as the intractability of rapid phase changes may compromise the input to the system. This paper introduces the design of a set of binary encoded computer generated holograms (CGHs) for real-time five-frame temporal phase shifting interferometry using a binary amplitude spatial light modulator.It is suitable for portable devices with constraints in computational power. The new set of binary encoded CGHs is used for measuring the phase of the generated electric field for a real-time selective launch in multimode fiber. The processing time for the new set of CGHs was reduced by up to 65% relative to the original encoding scheme.The results obtained from the new interferometric technique are in good agreement with the results obtained by phase shifting by means of a piezo driven flat mirror.